Semi-Immersive Virtual Reality: Distracting Children with Cancer from the Side Effects of Post-Chemotherapy - Margaretha, Sumarti; Widiastuti, Zeni; Purwaningsih, Iswanti (Advances in Cancer Science, 2025)
This study aims to explore the role of semi-immersive virtual reality (VR) as a non-pharmacological distraction technique to alleviate post-chemotherapy side effects among pediatric cancer patients. Using a qualitative descriptive approach through a library-based study, data were collected from peer-reviewed journal articles, clinical reports, and systematic reviews published between 2018 and 2025. The data analysis involved thematic identification, data reduction, categorization, and inductive interpretation to synthesize conceptual and empirical findings. The results reveal that both immersive and semi-immersive VR significantly reduce chemotherapy-related anxiety, pain, nausea, and emotional distress in children, with semi-immersive systems demonstrating comparable efficacy to immersive ones while offering greater practicality and fewer adverse effects. Semi-immersive VR also enhances engagement, emotional well-being, and perceived control during treatment, contributing to improved psychological adaptation. These findings affirm the theoretical basis of the Gate Control Theory of Pain and the Cognitive-Behavioral Distraction Model, highlighting VR’s effectiveness in modulating sensory and emotional responses to medical stressors. The study concludes that semi-immersive VR represents an innovative, feasible, and child-friendly therapeutic adjunct in pediatric oncology care. The implications extend to healthcare practice, where VR can be integrated as a supportive digital therapy, and to future research, which should employ triangulated, longitudinal approaches to evaluate its long-term psychosocial benefits.